Anemone bleaching impacts the larval recruitment success of an anemone-associated fish - Marc Besson; William E. Feeney; Camille Gache; Duncan A. O’Brien; Cécile Berthe; Zara-Louise Cowan; Rohan M. Brooker; Vincent Laudet; David Lecchini (Coral Reefs, 2023)
In marine environments, mutualisms such as those between corals or sea anemones and their algal symbionts (Symbiodiniaceae) play a key role for supporting surrounding biodiversity. However, as the breakdown of the mutualism between corals and/or anemones and Symbiodiniaceae (i.e. bleaching) become increasingly frequent and severe, the risk of losing the additional species that rely on them may also increase. While the effects of anemone bleaching on the biology and ecology of anemone-associated fishes have been the subject of recent research, relatively little is known about the impacts that anemone bleaching might have on the recruitment of larval fish. Here, we report that climate change-induced anemone bleaching impairs a secondary mutualism between anemones and an anemone-associated fish species, the threespot dascyllus ( Dascyllus trimaculatus ). Field-based monitoring over a 1-year period showed anemones that bleached experienced decreased recruitment of larval D. trimaculatus compared to those that did not bleach, with abundances of newly settled D. trimaculatus three times lower in bleached versus unbleached anemones. A visual choice experiment showed that this pattern is associated with fish being less attracted to bleached anemones, and a predation experiment demonstrated that fish associated with bleached anemones experienced higher mortality compared to those associated with unbleached anemones. These results suggests that the decreased recruitment of D. trimaculatus observed in bleached anemones may be driven by hampered pre-settlement (habitat selection) and post-settlement (survival to predation) processes for larval D. trimaculatus in bleached hosts. This study highlights the risk of cascading mutualism breakdowns in coral reefs as conditions deteriorate and stresses the importance of protecting these mutualisms for the maintenance of coral reef biodiversity.

Complete and rapid reversal of the body color pattern in juveniles of the convict surgeonfish Acanthurus triostegus at Moorea Island (French Polynesia) - Marc Besson; Pauline Salis; Vincent Laudet; David Lecchini (Coral Reefs, 2018)